Evaluation of marine ecological civilization construction and its spatial correlation network in China’s coastal province from the perspective of land-sea coordination - Gao, Kun; Yu, Lianghong (Frontiers in Marine Science, 2024)
The marine ecological civilization construction (MECC) plays an indispensable role in the development of ecological civilization in China. With the growth of the marine economy, threats to ecological environment have been increasing. From the standpoint of land-sea coordination, this study evaluates the MECC in China's coastal province and employs social network analysis to explore the spatial correlation network structure and radiation capacity. The results show that: (1) The MECC in China's coastal provinces has exhibited a general upward trend with occasional fluctuations. However, the subsystems exhibit disparate developmental trends, with the pressure subsystem exhibiting a slight decline. (2) While the MECC of all coastal provinces has increased, the MECC of China's coastal provinces exhibits considerable variation, with each facing different development challenges. (3) The spatial correlations of the MECC among coastal provinces have become increasingly pronounced, particularly in the regions surrounding Hangzhou Bay and Bohai Bay, while long-distance trans-regional correlations are relatively weaker. (4) There have been notable improvements in the MECC radiation capacity of all provinces, most prominently in Shanghai, Zhejiang, Jiangsu, and Shandong, which currently rank among the highest in the country. Conversely, the MECC radiation capacity of Liaoning, Hebei, Fujian, and Hainan remains relatively underdeveloped. The results indicate that while the MECC has developed, it still encounters obstacles pertaining to regional disparities, subsystem challenges, and spatial correlation development. The study concludes with a series of recommendations aimed at fostering sustainable development of the MECC in China's coastal regions.